Pantoum as Transactional Communication Tactic in Lok Baintan Floating Market - Ayu Hamdani; Latifa Ramonita; Dewi Rachmawati (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
The Lok Baintan Floating Market in South Kalimantan, is a unique tourist destination where local residents have been trading goods on the water for hundreds of years. The people there have been buying and selling on the Lok Baintan River since ancient times, previously using a barter system. One noteworthy feature of vendors' conduct at the market is their frequent utilization of pantoum as a tactic to enhance the interest of visitors. From a tourism perspective, this is an interesting and unique place to visit. With reference to transactional communication theory, this study intends to find out the tactics used by the vendors in the Floating Market when utilizing pantoum. Methodology research to gather as much information as possible about the issue, this study employs the qualitative research approach through document analysis and deep interviewing to relevant informants, consist of 10 informats, 5 Acil pantoum, 1 tourism government, 2 head of community and 2 visitors, The study's findings demonstrate that the utilization of pantoum in transactional communication at the Lok Baintan floating market benefits the vendors by providing a distinctive tourist attraction and thus, creating a chance for increased revenue and create good relationship. Not to mention, this practice might be seen as a means of maintaining a sustainable culture. As well this research shows an overview of how a rhyme culture can attract tourists and maintain a sustainable culture.